Conceptualizing Restorative Justice Based on Progressive Law: A Philosophical Contribution Towards Strengthening Human Security Guarantee in the National Legal System - Agam Ibnu Asa; Hendri Irawan (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2026)
This article addresses the rigidity of the positive legal system, which tends to be positivistic and is deemed less adaptive in responding to complex humanitarian issues and concerns regarding Human Security. The primary goal is to analyze and philosophically elaborate the concept of Restorative Justice imbued with the spirit of Progressive Law as a theoretical framework to strengthen the guarantee of Human Security within the national legal system. The method employed is normative-constructive legal philosophy analysis through an in-depth review of Satjipto Rahardjo’s thoughts and Restorative Justice literature. The analysis reveals that Restorative Justice, from the perspective of Progressive Law, transforms from merely an alternative mechanism into a critical paradigm. This paradigm shifts the legal focus from offender punishment (retributive justice) towards restoration of social relations, victim healing, and conflict prevention rooted in humanitarian values. This philosophical contribution provides an essential foundation for criminal justice reform oriented toward substantive justice and fulfillment of human dignity. In conclusion, the implementation of Restorative Justice based on Progressive Law is crucial for transforming the national legal system, not only to ensure order but, fundamentally, to strengthen Human Security by placing restoration and humanity at the core of all law enforcement processes.